2019
DOI: 10.5664/jcsm.7636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obstructive Sleep Apnea in Joint Hypermobility Syndrome: A Systematic Review and Meta-Analysis

Abstract: Study Objectives: Because of associated abnormalities affecting connective tissue in various organs including airways, hypermobility syndrome has been associated with high risk for the development sleep apnea. Ehlers-Danlos syndrome (EDS) and Marfan syndrome (MFS) represent the most common hypermobility syndromes; therefore, the purpose of this review was to examine the prevalence of obstructive sleep apnea (OSA) in these populations. Methods: All publications and poster presentations written in English found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
0
18
1
1
Order By: Relevance
“…By contrast, previous research in subjects with EDS showed a higher prevalence of obstructive sleep apnea measured by polysomnography or respiratory polygraphy [14,16,18]. However, to our knowledge, no other studies concerning sleep measured by accelerometry in adults with hEDS and G-HSD have been performed with which we can compare our results.…”
Section: Sleepcontrasting
confidence: 91%
See 1 more Smart Citation
“…By contrast, previous research in subjects with EDS showed a higher prevalence of obstructive sleep apnea measured by polysomnography or respiratory polygraphy [14,16,18]. However, to our knowledge, no other studies concerning sleep measured by accelerometry in adults with hEDS and G-HSD have been performed with which we can compare our results.…”
Section: Sleepcontrasting
confidence: 91%
“…In turn, reduced physical activity may lead to impaired sleep quality in hEDS/HSD, as these are bidirectionally related in the general population [11][12][13]. Moreover, impaired sleep quality has been observed in patients with symptomatic GJH, reflected as a higher prevalence of obstructive sleep apnea and snoring, problems of maintaining sleep and not feeling refreshed in the morning [14,15]. Gaisl et al (2017) have shown that these sleeping problems have a major impact on their health-related quality of life [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in OSA, the suppleness of tissues in upper airways makes them more collapsible that might also be the reason for its increased association with FES. Furthermore, OSA is common in connective tissue disorders, 54,55 as indicated from its association with Ehler Danlos and Marfan's syndrome, 56 Loeys-Dietz syndrome, 57 and Cutis-laxa associated with hereditary amyloidosis. 58 Thus, connective tissue disorders may predispose patients to OSA, which is associated with a structural alteration of the extracellular matrix of upper airway tissue, and a positive correlation has been reported between elastin fiber network disorganization score and apnea-hypopnea index.…”
Section: Glaucoma and Obstructive Sleep Apneamentioning
confidence: 99%
“…Within the noncardiovascular features, obstructive sleep apnea (OSA) seems to be highly prevalent in Marfan syndrome. The prevalence rate of OSA reported is 59.7% among adults (Apnea Hypopnea Index cutoff of five events/h) [ 7 ] and 80% among children (Apnea Hypopnea Index cutoff of one event/h) [ 8 ]. In Marfan syndrome patients, the underlying cause of OSA is not well elucidated but might be related to specific craniofacial features and higher upper airway collapsibility [ 9 ].…”
Section: Introductionmentioning
confidence: 99%